Output current ripple analysis of single phase inverter with discontinuous PWM - Muqorobin, Anwar; Wijanarko, Sulistyo; Santosa, Harjono Priyo; Irawati, Indrarini Dyah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Voltage source inverter has been applied for uninterruptible power supply (UPS), renewable energy sources, and motor drive. The popular modulations for inverters are sinusoidal pulse width modulation (SPWM), zero sequence signal modulation (ZSS), space vector modulation (SVM), and discontinuous PWM (DPWM). All these modulations have been applied to three-phase and multiphase inverters. The characteristics of the modulation application in these inverters have been well investigated. However, only SPWM has been applied satisfactorily in single-phase inverter. From the literature, the applications of ZSS and DPWM couldn’t show any benefit. In this paper, a DPWM is proposed for single-phase inverter. The output current ripple is analyzed and experiments are conducted to verify the analytical result. Comparison to SPWM is conducted to find the modulation index range that provides a benefit when using the DPWM.